Factors Associated With Acceptance of Telehealth-Based Antimicrobial Stewardship Program Recommendations in a Community Hospital Health System. (3rd September 2022) - Shively, Nathan R; Jacobs, Max W; Moffa, Matthew A; Schorr, Rebecca E; Walsh, Thomas L
Abstract: Background: Telehealth-based antimicrobial stewardship programs (TeleASPs) have led to reduced broad-spectrum antimicrobial utilization. Data on factors associated with acceptance of stewardship recommendations are limited. Methods: A TeleASP, facilitated by remote infectious disease physicians and local pharmacists, was implemented in 2 community hospitals from February 2018 through July 2020. Variables potentially affecting acceptance of TeleASP recommendations were tracked. Odds ratios of acceptance were determined utilizing multiple logistic regression. Results: During the 30-month period, 4863 (91.2%) of the total 5333 recommendations were accepted. Factors associated with a higher odds of acceptance in multivariable analysis were recommendations for antimicrobial dose/frequency adjustment (odds ratio [OR], 2.63; 95% CI, 1.6–4.3) and order for labs/tests (OR, 3.30; 95% CI, 2.1–5.2), while recommendations for antimicrobial de-escalation (OR, 0.75; 95% CI, 0.60–0.95) and antimicrobial discontinuation (OR, 0.57; 95% CI, 0.42–0.76) were associated with lower odds of acceptance. Female physicians were more likely to accept recommendations compared with males (93.1% vs 90.3% acceptance; OR, 1.65; 95% CI, 1.3–2.2). Compared with physicians with <3 years of experience, who had the highest acceptance rate (96.3%), physicians with ≥21 years of experience had the lowest (87.1%; OR, 0.26; 95% CI, 0.15–0.45). Conclusions: TeleASP recommendations were accepted at a high rate. Acceptance rates were higher among female physicians, and recommendations to stop or de-escalate antimicrobials led to lower acceptance. Recommendations made to the most experienced physicians were the least accepted, which may be an important factor for stewardship programs to consider in education and intervention efforts. Abstract : We evaluated variables impacting acceptance of stewardship recommendations at two community hospitals. Recommendations to stop or de-escalate antimicrobials led to lower acceptance Female physicians were more likely to accept recommendations, and recommendations to the most experienced physicians were least accepted.